2002
DOI: 10.1177/154193120204602622
|View full text |Cite
|
Sign up to set email alerts
|

Training in a Virtual Stereoscopic Environment

Abstract: This study investigated transfer-of-training for a pick-and-place task in monoscopic, stereoscopic, and real-world environments. Ten training trials were given to 30 subjects in the three environments (10 subjects each). The averages of task completion time in the stereoscopic and real-world environments were less than those in the monoscopic environment. In a post-training real-world trial, there were no differences due to the training environment (including another group of 10 subjects who received no traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…For example, stereo presentations reduced the required training time of a teleoperating task (Drascic, 1991). Mourant and Parsi (2002) found that people who trained a pick-and-place task in a stereo environment performed better on one aspect of a real world posttest than participants who had trained in a monoscopic environment. An experiment of Luursema et al (2008) found that computer-implemented stereopsis provided a small positive effect on learning of anatomy in the medical field.…”
Section: Effects Of Stereo On Performance and Learningmentioning
confidence: 99%
“…For example, stereo presentations reduced the required training time of a teleoperating task (Drascic, 1991). Mourant and Parsi (2002) found that people who trained a pick-and-place task in a stereo environment performed better on one aspect of a real world posttest than participants who had trained in a monoscopic environment. An experiment of Luursema et al (2008) found that computer-implemented stereopsis provided a small positive effect on learning of anatomy in the medical field.…”
Section: Effects Of Stereo On Performance and Learningmentioning
confidence: 99%